Study on prediction fly ash generation using statistical method - Zahari N.M.; Mohamad D.; Arenandan V.; Beddu S.; Sadon S.N.; Syamsir A.; Kamal N.L.M.; Zainoodin M.M.; Nadhirah A. (American Institute of Physics Inc., 2023)
This study present of fly ash generation at generated one the power plant in Malaysia. The main purpose of this research to predict the generation of fly ash in future years by a method. This prediction is important so that fly ash generated could be used in a beneficial way. Prediction of fly ash was done by using two types of software which are Neural Network Toolbox, MATLAB and IBM SPSS Statistics 23, Linear Regression. Among these two methods, IBM SPSS Statistics 23, Linear Regression is found to be the most effective way to predict the generation of fly ash in the future by using five year's best fit linear regression equation compared to Neural Network Toolbox, MATLAB. 2018 Author(s).